فجوة التوقع في بيئة المراجعة بين المسببات وسُبل المعالجة - عبداللاوي, مفيد (جامعة الوادي - University of Eloued, 2014)
فجوة التوقعات في بيئة المراجعة أو ببساطة "فجوة التوقعات" هي مصطلح يستخدم للدلالة على الفرق في توقعات مستخدمي القوائم المالية وتوقع مدقق الحسابات في ما يتعلق بتدقيق القوائم المالية. ويمكننا أيضا أن نفسرها على أنها تمثل الفرق بين ما يعتقده مستخدمو المعلومات المالية حول فعالية عملية المراجعة وما يعتقد المدقق، ويمكن أيضا أن تفسر على أنها تنتج عن الفرق بين توقعات المستخدم والمراجع نفسه على مسؤوليات المدقق، ويمكن أيضا أن ترجع إلى الاختلاف في الفهم بشأن طبيعة عملية المراجعة. والمطلوب من المدقق الحد من مخاطر المراجعة إلى مستوى منخفض مقبول للحصول على تأكيد معقول، ولكن ما هو معقول؟ هذا يمكن أن يكون مختلفا من وجهتي نظر المدقق ومستخدمي القوائم المالية وهذا ما يخلق فجوة التوقعات. Auditing expectation gap or simply expectation gap is the term used to signify the difference in expectations of users of financial statements and auditor’s expectation concerning audited financial statements. Expectation gap can also be explained as the difference between the effectiveness of audit engagement what users believe and what auditor believes. Expectation gap in related to audit can also be explained as the difference between expectation of user and auditor himself on the responsibilities of the auditor. It can also refer to difference in understanding regarding nature of audit engagement what users believe audit is and what audit actually is. Auditor is required to reduce audit risk to an acceptably low level to attain reasonable assurance. But what is reasonable? This can be different in the eyes of auditor and in the eyes of users of financial statements and this creates expectation gap.
The Audit Expectations gap between the causes and solutions
مقال
Keywords: فجوة التوقعات ، بيئة المراجعة، القوائم المالية ، مدقق الحسابات، تدقيق القوائم المالية.